EVALUATION OF HEAVY HEAVY METALS POLLUTION IN SOIL AND LETTUCE OBTAINED FROM IRRIGATED DUMPSITES IN MUBI NORTH ADAMAWA STATE, NIGERIA - Chindapi, Hyelnasinyi; Danbaki, Shinggu Yamta; Birma, Bwatanglang Ibrahim; Jonathan, David Ujewe (FUDMA JOURNAL OF SCIENCES, 2026)
In Mubi, Nigeria, dumpsite soils are commonly used as organic manure to enhance soil properties and crop yield, but they often contain hazardous heavy metals. This study assessed heavy metal concentration, transfer, and pollution in soils and lettuce from three dumpsites. Key findings show transfer factors of 0.59–0.89, with copper, cadmium, and chromium being most mobile. The pollution load index exceeded 1 at all sites, indicating soil deterioration, with contamination highest at Mayanka. Geo-accumulation indices revealed moderate to high pollution for manganese, cadmium, copper, and zinc from anthropogenic sources. Contamination factors ranged from 0.87 to 12.35, and the degree of contamination surpassed 24, classifying sites as highly contaminated. However, enrichment factors remained below 2, suggesting minimal enrichment. The study highlights cumulative anthropogenic contamination and elevated metal transfer, posing risks to the food chain and underscoring the need for cautious management of dumpsite soils in agriculture.